Excited state proton transfer in the triplet state of 8-hydroxy-5-nitroquinoline: a transient absorption and time-resolved resonance Raman spectroscopic study. Issue 1 (8th December 2022) - Wang, Ran; Zhang, Fengjin; Pan, Xinghang; Zheng, Xuming; Xue, Jiadan; Du, Yong; Xie, Binbin
Abstract : 8-Hydroxy-5-nitroquinoline is an antimicrobial, anti-inflammatory and anticancer agent. Our findings on its photochemistry reveal that it tautomerizes and dissociates in the excited state, suggesting the drug delivered should be protected from light. Abstract : 8-Hydroxy-5-nitroquinoline (NO2 -QN-OH) is an antimicrobial, anti-inflammatory and anticancer agent, and has been approved for use in the treatment of diseases. Its photosensitivity, however, cannot be overlooked. The photochemistry of 8-hydroxy-5-nitroquinoline in acetonitrile is investigated using transient absorption and time-resolved resonance Raman spectroscopies. By identifying the short-lived intermediates during the photoreaction, it is clear that the T n state NO2 -QN-OH is generated in 0.8 ps via an ultrafast ISC, followed by the IC in 8.5 ps to produce the T1 state. In neat acetonitrile, the T1 state NO2 -QN-OH undergoes intramolecular proton transfer and tautomerizes to form T1 state NO2 -QNH-O. To our knowledge, this is the first time that the intramolecular excited state proton transfer of hydroxyl-quinolines in an aprotic polar solvent is observed.